Hitman's wife's bodyguard [videorecording (DVD)] - Reynolds, Ryan; Jackson, Samuel L.; Hayek, Salma, 1966-; Banderas, Antonio; Freeman, Morgan (Lionsgate, 2021)
In The Hitman's Wife's Bodyguard -- bodyguard Michael Bryce, hitman Darius Kincaid and his wife Sonia are back as the mismatched, high-octane trio -- that are once again forced together into another life-threatening mission to save Europe from a vengeful and powerful zealot.